ESTABLISHING THE TECHNICAL ADVANCES APPLIED DEMONSTRATION OF SERICULTURE PRODUCTION IN YEN BAI PROVINCE (Vietnam Journal of Agriculture and Environment, 2023)
Yen Bai province is considered as one of the few locations with largely concentrated areas under sericulture cultivation Sericulture production has provided abundant jobs and opportunities for local residents, improved the lives of many households and reduced poverty in the area. The application of technological advances through large scale demonstrations is proved to be the best way for improving the economic efficiency of sericulture. In the duration of three years (2020 - 2022), 09 sericulture demonstrations covering a total area of 197.4 ha under mulberry cultivation have been established and developedwith the participation of 370 local households, producing 11,562 silkworm egg cards in Van Chan and Tran Yen districts, Yen Bai province. Results conducted from the study showed that these demonstrations made a positive impact to the production of mulberry and silkworm as indicated by the increase of mulberry leaf and cocoon yield (21.89% and 13% higher than normal, respectively). In addition, the cocoon harvesting time reduced to 67.19%, the rate of good cocoon increased by 7.19%. 100% of the sericulture farmers are using wooden square mountages.